Prophecy in Plutarch and Philo of Alexandria - Klem, Matthew J. (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2024)
David Winston distinguishes two types of Mosaic prophecy in Philo’s De vita Mosis, noetic and ecstatic. Noetic prophecy, which corresponds to Moses’s delivery of the special laws, is active and rational. Ecstatic prophecy, which corresponds to Moses’s predictive prophecies, is passive and irrational, though while some Greek authors view ecstasy in terms of a total possession by the god, Philo takes a more moderate view that can also be found in Plutarch. Winston’s appeal to Plutarch is the basis of this article. It explores ecstasy in Plutarch’s two dialogues on the Pythian oracle and applies Plutarch’s categories to Mosaic prophecy in De vita Mosis. In light of Plutarch’s discussion, noetic prophecy is actually passive, and ecstatic prophecy is actually active.